COMPARATIVE ADVANTAGE OF DAIRY FARMING IN LEVERAGING THE RELIEF OF RURAL COMMUNITIES FROM POVERTY TRAP: AN EVIDENCE FROM RURAL TAMIL NADU - G. Senthil Kumar; K.N. Selvakumar; M. Prabu; A. Serma Saravana Pandian; C. Valli; B. Jayavarathan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An attempt was made to measure the comparative advantage of dairy farming among different occupational groups of rural Tamil Nadu (540 households and 2500 persons) for its poverty alleviation role. The most commonly used measures of poverty viz., head count index (P 0), poverty gap index (P1) and squared poverty gap (poverty severity) index (P2), the Watts index and average exit time from poverty were calculated. About 59 per cent of the total sample households and close to 65 per cent of sample population were found to stay below poverty line. P1 P2 and W index were observed to be the highest among agricultural labourers and the lowest among dairy farmers. At four per cent of hypothetical income growth rate, the time required to exit out of poverty was estimated to be the least for dairy farmers (4.66 years for buffalo and 4.91 years for cattle), followed by fishermen (5.09 years). Keeping in view of poverty reduction potential of dairy farming, it shall be included in poverty alleviation programmes.